Services, technologies, and systems at Ka band and beyond-a survey. - Gargione, F.
This paper discusses system and technology aspects crucial to the development of satellite communications at Ka band (20-30 GHz) and beyond. It surveys the evolution of Ka band geostationary Earth orbit (GEO) satellite communications until the present stage of development of systems for direct-to-user (DTU) provision of interactive multimedia services worldwide. Then it discusses the attenuation problem and main technical issues of this new technology. Finally, it provides a view on experiments and technological developments at extremely high-frequency (EHF) bands
Keywords: 20 to 30 GHz; EHF bands; GEO; Ka band; SHF; Direct-to-user services; Experiments; Extremely high-frequency.; Geostationary Earth orbit; Interactive multimedia services; Rain attenuation problem; Satellite communication services; Satellite technologies; Survey; Systems